2023
DOI: 10.1212/cpj.0000000000200123
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Related Concussion

Abstract: Purpose of ReviewThe incidence of sport-related concussion (SRC) has been increasing in different sports and its impact on long-term cognitive function is increasingly recognized. In this study, we review the epidemiology, neuropathophysiology, clinical symptoms, and long-term consequences of SRC with a specific focus on cognition.Recent FindingsRepeated concussions are associated with an increased risk of several neurologic diseases and long-term cognitive deficits. To improve cognitive outcomes in athletes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…45 Consequently, studies of rehabilitation methods must carefully balance their study populations to provide usable results, 34,46,47 especially with these interindividual differences. 48 The assessments help with diagnostics and RTP grading of an SRC, but it could be argued that it doesn't help players holistically. For example, for muscle or tendon injuries, there is a clear guideline that actively (isometric contraction, tens, stretching, strengthening) rehabilitees the injured tissue before returning to play.…”
Section: Discussionmentioning
confidence: 99%
“…45 Consequently, studies of rehabilitation methods must carefully balance their study populations to provide usable results, 34,46,47 especially with these interindividual differences. 48 The assessments help with diagnostics and RTP grading of an SRC, but it could be argued that it doesn't help players holistically. For example, for muscle or tendon injuries, there is a clear guideline that actively (isometric contraction, tens, stretching, strengthening) rehabilitees the injured tissue before returning to play.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the current research surrounding concussions stems from data on sports-related concussions (SRC). Sports-related concussions are common, but only account for 20% – 25% of all 3.7 million patients who present to casualty with a head injury in the United States annually, despite high participation rates (Harmon et al 2013, cited in Hallock et al 2023 ). Although the true incidence is not known, it has been estimated that about 33 million children worldwide sustain concussions annually (Davis et al 2017 ).…”
Section: A Little Background Into Concussionmentioning
confidence: 99%
“…The refinement of this approach could eventually lead to a non-invasive, sideline adjunct test for SRC (Hicks et al 2023 ). Currently, it is reported that at least 50% of concussions remain undiagnosed (Harmon et al 2013 cited in Hallock et al 2023 ).…”
Section: A Little Background Into Concussionmentioning
confidence: 99%
“…
The incidence of sport-related concussion (SRC) has increased in many team-based sports (1,2,3) , such as rugby, Gaelic (camogie, hurling and football), and hockey in Ireland (3,4) . Following SRC, the brain becomes injured, its function disrupted, and an "energy crisis" (5) occurs.
…”
mentioning
confidence: 99%
“…This research developed insight on PD/PN's (1) awareness, knowledge and (2) implementation of nutritional supports in concussion recovery with athletes. There was a clear contrast between participants who had an awareness and knowledge of the importance of nutrition in supporting brain recovery after a concussion and those who did not.…”
mentioning
confidence: 99%